Insufficient university policies on scientific integrity and their relationship with the denial of institutional licensing - Muñoz del Carpio-Toia , Agueda (2023)
The aim of this study was to analyze the relation between institutional policies on scientific integrity and licensing of Peruvian universities. It is a descriptive study analyzing Peruvian regulations on university quality assessment, university licensing (accreditation), scientific integrity regulations and the denial of university operating licenses. It was found that, of the 48 universities and 2 graduate schools that did not meet the Basic Quality Conditions under the Peruvian Institutional Licensing Model, 32 universities and 1 graduate school (66%) had deficiencies related to required scientific integrity policies. The study concludes that universities’ scientific integrity policies are an important criterion for receiving Institutional Licensing in the Peruvian university system.